1992
DOI: 10.1128/jb.174.2.508-513.1992
|View full text |Cite
|
Sign up to set email alerts
|

Overproduction of beta-ketoacyl-acyl carrier protein synthase I imparts thiolactomycin resistance to Escherichia coli K-12

Abstract: Thiolactomycin [(4S)(2E,5E)-2,4,6-trimethyl-3-hydroxy-2,5,7-octatriene-4-thiolide] (TLM) is a unique antibiotic structure that inhibits dissociated type II fatty acid synthase systems but not the multifunctional type I fatty acid synthases found in mammals. We screened an Escherichia coli genomic library for recombinant plasmids that impart TLM resistance to a TLM-sensitive strain of E. coli K-12. Nine independent plasmids were isolated, and all possessed a functional I8-ketoacyl-acyl carrier protein synthase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
115
0
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(123 citation statements)
references
References 29 publications
6
115
0
2
Order By: Relevance
“…For instance, recombinant cells with increased doses of murZ, the E. coli gene encoding UDP-GlcNAc enolpyruvate transferase, displayed phosphomycin resistance (8). Clones resistant to thiolactomycin were found to contain increased levels of fabB, which encodes ␤-ketoacyl-acyl carrier protein synthase I, the cellular target of thiolactomycin (9). Increased levels of prolipoprotein signal peptidase rendered cells resistant to globomycin, a specific inhibitor of that enzyme (10).…”
mentioning
confidence: 99%
“…For instance, recombinant cells with increased doses of murZ, the E. coli gene encoding UDP-GlcNAc enolpyruvate transferase, displayed phosphomycin resistance (8). Clones resistant to thiolactomycin were found to contain increased levels of fabB, which encodes ␤-ketoacyl-acyl carrier protein synthase I, the cellular target of thiolactomycin (9). Increased levels of prolipoprotein signal peptidase rendered cells resistant to globomycin, a specific inhibitor of that enzyme (10).…”
mentioning
confidence: 99%
“…Turnowsky and colleagues [39] demonstrated that overexpression of EnvM (FabI) protein from the plasmid-borne gene conferred resistance to diazaborine, a specific inhibitor for FabI. Tsay and coworkers [40] screened a thiolactomycin sensitive E. coli strain against an E. coli genomic library for recombinant plasmids that conferred resistance to thiolactomycin, an inhibitor for FabB protein (β-ketoacyl-acyl carrier protein synthase I). They isolated nine plasmids, all of which contain a functional fabB gene.…”
Section: Discussionmentioning
confidence: 99%
“…They isolated nine plasmids, all of which contain a functional fabB gene. Over-expression of FabB protein appeared to lead to increased resistance to thiolactomycin in E. coli [40]. Apfel and colleagues [41] demonstrated that over-expression of peptide deformylase in a cell reduced its susceptibility to inhibitors specific for the essential target, peptide deformylase.…”
Section: Discussionmentioning
confidence: 99%
“…The fabH encodes ␤-ketoacyl-acyl carrier protein synthase III (KAS III), which catalyzes the condensation reaction during the initial step of fatty acid biosynthesis [23]. Previous studies found that the KAS III deficient E. coli strain had a higher UFA proportion compared with the wild type strain, especially the monounsaturated fatty acid with 18 carbons (18:1) [24]. The bacterial strains were stored in 25% sterilized glycerin at −80 • C. To prepare the bacterial suspension for PEC inactivation, the individual bacterial strain was streaked on a nutrient agar plate and incubated to acquire isolated colonies.…”
Section: Photoelectrocatalytic Inactivation Apparatus Setupmentioning
confidence: 99%
“…The FA profiles of three E. coli strains were first determined to confirm the target mutations; Table S2 shows the results. Before PEC treatment, the parental strain E. coli BW25113 showed a typical E. coli fatty acid profile [16,24], with palmitic acid (16:0) as the dominant congener (45.6%), followed by monounsaturated fatty acids such as hexadecenoic acid (16:1, 12.1%) and octadecenoic acid (18:1, 22.9%). Compared with the parental strain, the mutants showed no difference in aspect of the total fatty acid content, but with different composition profiles.…”
Section: Fatty Acid Profilementioning
confidence: 99%